2016
DOI: 10.4491/eer.2016.094
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption isotherm and kinetics analysis of hexavalent chromium and mercury on mustard oil cake

Abstract: The biosorption process has been established as characteristics of dead biomasses of both cellulosic and microbial origin to bind metal ion pollutants from aqueous suspension. The high effectiveness of this process even at low metal concentration, similarity to ion exchange treatment process, but cheaper and greener alternative to conventional techniques have resulted in a mature biosorption technology. Yet its adoption to large scale industrial wastewaters treatment has still been a distant reality. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 133 publications
1
6
0
Order By: Relevance
“…The nitrogen adsorption/desorption isotherm of samples synthesised under optimal electrospinning conditions was shown in Figure 6. The adsorption/desorption of the samples is similar to the second-kind of isotherms, demonstrating the meso-nature of the porous size distribution for the compound, according to the results (Reddy et al, 2017). Furthermore, BET curve results show that the samples have a specific surface area of about 273 m 2 /g.…”
Section: Textural Propertiessupporting
confidence: 73%
“…The nitrogen adsorption/desorption isotherm of samples synthesised under optimal electrospinning conditions was shown in Figure 6. The adsorption/desorption of the samples is similar to the second-kind of isotherms, demonstrating the meso-nature of the porous size distribution for the compound, according to the results (Reddy et al, 2017). Furthermore, BET curve results show that the samples have a specific surface area of about 273 m 2 /g.…”
Section: Textural Propertiessupporting
confidence: 73%
“…Many previous studies have shown that NaOH solutions are highly efficient for desorbing Cr(VI) from loaded sorbents (Debnath, Maity, & Pillay, 2014;Hui, Chao, & Kot, 2005;Reddy, Chauhan, & Chakraborty, 2016). Fig.…”
Section: Metal Desorption and Recycling Of Alginate/pei Membranesmentioning
confidence: 93%
“…However, the increase of pH also increases the reduction of Cr(VI) to the positively charged Cr(III). Adsorption of Cr(III) species onto protonated CKSC and Fe-C-CKSC surface decreased due to the fact that the opposite charges repel each other [43]. The mechanisms of removal of Cr(VI) by Fe-C-CKSC include mainly electrostatic attraction between protonated adsorbent surface (-OH 2 + and -NH 3 + groups) and Cr(VI) species, ligand exchange of Cr(VI) species and re-sorption of Cr(III) reduced from Cr(VI) via chelation.…”
Section: Effect Of Solution Ph On Adsorptionmentioning
confidence: 99%